Pengaruh Artificil Intelligence (AI) Pembelajaran PAI terhadap Prestasi Belajar di SMP Daarul Istiqlal - Rahmat Hidayat Aqsho. S; Khairuddin Lubis; Dewi Sundari (Journal of Innovative and Creativity, 2025)
This research aims to discover and analyze : The Influence of Artificial Intelligence (AI) in Pai learning on Acdemic Achievement at Daarul Istiqlal. The sample in this study consists of 60 students from SMP Daarul Istiqlal, which was determined using a saturated sampling methood, meaning the entire population was tudents totaling 60 people who were counted using a type of sample, namely using the entire population as the sample. The data collection techniques used were observation and distribution of questionnaires/surveys. This research uses a quantitative method, namely by presenting research results in the form of numbers or statistics to test hypotheses with the help of the SPSS version 22 for Windows program. The research results of the variable influence of Artificial Intelligence have a positive and significant influence on the learning achievement of Islamic religious education for students in class VII and VIII of SMP Daarul Istiqlal Medan, meaning that the hypothesis in this study is accepted as proven by the calculated t value > t table (2.427> 1.671) and the variable influence of Artificial Intelligence. Intelligence is able to influence the Islamic religious education learning achievement variable for students in class VII and VIII at Daarul Istiqlal Middle School by 92%, while 8% of students are filled with other variables that were not examined in this research.